1995
DOI: 10.1172/jci118250
|View full text |Cite
|
Sign up to set email alerts
|

Intratracheal instillation of keratinocyte growth factor decreases hyperoxia-induced mortality in rats.

Abstract: Alveolar type II cell proliferation occurs after many forms of lung injury and is thought to play a critical role in alveolar epithelial repair. Keratinocyte growth factor/fibroblast growth factor 7 (KGF) has been shown to promote alveolar type II cell growth in primary culture and alveolar epithelial hyperplasia in vivo. In this study, we used immunohistochemical analysis to determine the intrapulmonary distribution and cellular localization of recombinant human KGF (rhKGF) instilled into the trachea of rats.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
190
3
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(206 citation statements)
references
References 48 publications
10
190
3
1
Order By: Relevance
“…In contrast, the number of cells in control samples decreased throughout time likely due to cell death. In agreement with previous studies, [15][16][17][18][19][20][21] these results suggest that in addition to promoting proliferation, KGF, P-KGF, and PL-P-KGF may also promote cell survival.…”
Section: P-kgf and Plasmin-derived P-kgf Retain Biological Activitysupporting
confidence: 93%
“…In contrast, the number of cells in control samples decreased throughout time likely due to cell death. In agreement with previous studies, [15][16][17][18][19][20][21] these results suggest that in addition to promoting proliferation, KGF, P-KGF, and PL-P-KGF may also promote cell survival.…”
Section: P-kgf and Plasmin-derived P-kgf Retain Biological Activitysupporting
confidence: 93%
“…We were particularly interested in KGF because of work from our group as well as other investigators who have reported that KGF can reduce lung injury in small animal models of pulmonary edema. Recombinant KGF pretreatment reduced mortality following intra-tracheal instillation of hydrochloric acid (37), bleomycin (38), hyperoxia (39) and Pseudomonas aeruginosa (40). In models of acute permeability edema such as ␣-naphthylthiourea (41), P. aeruginosa (40) or ventilator-induced lung injury (42), KGF reduced lung edema and bronchoalveolar lavage protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…1 repair, and protect the lung from a variety of infectious and noninfectious insults (25)(26)(27)(28)(29)(30)(31). Our initial hypothesis in this study was that KGF administration would increase pulmonary collectin levels in the airspace and enhance the survival of mice challenged with IAV.…”
mentioning
confidence: 99%